Impact of Multimeric Ferrocene‐containing Cyclodecapeptide Scaffold on Host‐Guest Interactions at a β‐Cyclodextrin Covered Surface. Issue 21 (23rd August 2021) - Sanchez Perez, Enrique; Toor, Ritu; Bruyat, Pierrick; Cepeda, Céline; Degardin, Mélissa; Dejeu, Jérôme; Boturyn, Didier; Coche‐Guérente, Liliane
Abstract: Among non‐covalent bonds, the host‐guest interaction is an attractive way to attach biomolecules to solid surfaces since the binding strength can be tuned by the nature of host and guest partners or through the valency of the interaction. For that purpose, we synthesized cyclodecapeptide scaffolds exhibiting in a spatially controlled manner two independent domains enabling the multimeric presentation of guest molecules on one face and the other face enabling the potential grafting of a biomolecule of interest. In this work, we were interested in the β‐cyclodextrin/ferrocene inclusion complex formed on β‐CD monolayers functionalized surfaces. By using surface sensitive techniques such as quartz crystal microbalance and surface plasmon resonance, we quantified the influence of the guest valency on the stability of the inclusion complexes. The results show a drastic enhancement of the affinity with the gradual increase of guest valency. Considering that the sequential binding events are equal and independent, we applied the multivalent model developed by the Huskens group to extract intrinsic binding constants and an effective concentration of host. Abstract : Host‐guest interaction is a promising way of attaching biomolecules to solid surfaces since the binding strength is tunable by the nature of host and guest partners or through the interaction valency. Herein, the effect of multivalency based cyclodecapeptide scaffold on the host‐guest interaction strength is reported. The gradual increase of the guest valency improves the stability of the inclusion complex drastically.